The Serengeti rules the quest to discover how life works and why it matters - Carroll, Sean B. (Princeton University Press, 2016)
"How does life work? How does nature produce the right numbers of zebras and lions on the African savanna, or fish in the ocean? How do our bodies produce the right numbers of cells in our organs and bloodstream? In [this book] ... Sean Carroll tells the stories of the pioneering scientists who sought the answers to such simple yet profoundly important questions, and shows how their discoveries matter for our health and the health of the planet we depend upon"--Dust jacket flap.